(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Language models are tools that assist machines in comprehending natural languages. Several language models have been created to date, each designed to perform a specific task. One such model is the BERT model, which is distinguished from others by its advantages, achievements, and capabilities. This language model is renowned for its ability to perform various operations on texts and provide highly accurate results. As an example, it is important to note that BERT is a valuable tool for various practices, including emotion detection in texts and media, text and image classification, machine translation, language and speech recognition, spam detection, question answering, and text creation. This article discusses the history of BERT’s creation, the need for its development, and its potential applications. Additionally, this text answers questions about the functionality, training, and purpose of the BERT model. It can be concluded that implementing the BERT model yields effective results in natural language processing.